Success of Streptokinase in Diabetic Smokers with ST-Elevation Myocardial Infarction (STEMI) with Absence of Other Factors (Medical Forum Monthly, 2021)
Objective: The objective of this study was to find success of streptokinase in diabetic smokers with ST-Elevation Myocardial Infarction (STEMI) with absence of other factors.Study Design: Experimental studyPlace and Duration of Study: This study was conducted at the Punjab Institute of Cardiology, Lahore, Imran Idris Teaching Hospital Sialkot from Feb, 2018 to Aug, 2018.Materials and Methods: A total of 382 cases meeting inclusion criteria were taken in this study after approval from hospital ethical committee. After taking informed consent all data was taken from Emergency department of emergency department of Cardiology, Punjab Institute of cardiology Lahore, Imran Idris Teaching Hospital Sialkot. Basic demographer information of all cases such as age and their address, contact details were taken. Streptokinase was given to each patient at a dose of 1.5 million units, diluted in 100 ml of normal saline, in 1 hour. Informed written consent of the patient/attendant was taken. Success of Streptokinase (SK) was determined on ECG after 90 min as per operational definition. All data was collected by researchers them self on attached Performa.Results: The mean age of cases was 46.45 ± 11.44 years with minimum and maximum age as 25 and 65 years. There were 370(96.9%) male and 12(3.1%) female cases. According to operational definition, a total of 200(52.4%) cases had success while 182(47.6%) cases did not have success of medication.Conclusion: The frequency of success of streptokinase in diabetic smokers with ST-Elevation Myocardial Infarction (STEMI) with absence of other factors is 52.4%. So the cases with these conditions must be managed accordingly and the treatment strategies must be revisited in order to improve the treatment outcome of these cases.